Authenticity, Commodification of the Self, and Micro-Influencers: An in-depth analysis into the online identity construction of South African micro-influencers within the Western Cape - Bull, Joshua (Centre for Film and Media Studies, 2022)
The aim of this paper was to engage with the ways in which micro-influencers within the Western Cape construct their online identities on Instagram. Theories of critical political economy of the media, self-branding, and the commodification of the self were applied to the context of micro-influencer identity construction as a means of understanding the mediated relationships between influencers, the brands they collaborate with, the platform Instagram, and the ways in which these relationships effect the construction of their online identities. This study made use of individual interviews with micro-influencers, as well as a micro-influencer focus group session in order uncover the main themes in relation to the influencers' perceptions of their online activity. A qualitative content analysis was also performed on content posted by the sample of micro-influencers that coded for the influencers' uses of platform affordances, photographic content, and their identity construction within their images based on concepts of gender representation in the media by Goffman (1979) and Gill (2000). Central to the micro-influencers' notions of success on the platform, and their perceptions of processes of identity construction, was the concept of authenticity. However, the authenticity referenced by the influencers, focused more on processes of fostering the perception of authenticity within the minds of their audience towards the self they perform online, as opposed to acting in accordance with one's true self. It was also found that their performative online identities were predicated on processes of the commodification of the self. In this sense, the construction of the influencers' profiles was dictated by processes of the commodification of the self, and the influencers understanding of how to create the perception of authenticity within the minds of their followers towards their online self.